Ben & Zip : Two Short Friends - Linden, Joanne; Goldsmith, Tom (Brooklyn, NY : Flashlight Press, 2014)
A tribute to friendship, boardwalks, and summer at the beach, this storybook tells of Ben and Zip, two best friends who will keep readers laughing, cheering, and guessing until the very end.
Keywords: Dogs -- Juvenile fiction; Lost articles -- Juvenile fiction; Beaches -- Juvenile fiction; Boardwalks -- Juvenile fiction; Dogs -- Fiction; Lost and found possessions -- Fiction; Beaches -- Fiction; Boardwalks -- Fiction